Screening of Rhizobial Isolates of Leucaena leucocephala Lam. for Mimosine Degradation Ability - Meghvansi1,2; S.K. Mahna1, Syed Farook Ali1*, L.S. Rawat1, M.K. (Journal of Phytology, 2010)
Rhizobia can use mimosine as sources of carbon and nitrogen. In this study, an attempt has been made to evaluate the eleven rhizobial isolates of Leucaena leucocephala under arid and semi arid regions of Rajasthan for their relative mimosine degradation ability. It was observed that higher concentrations of mimosine adversely affected the growth, in terms of CFUs of rhizobial isolates. However, the trend of growth reduction was uneven and a few rhizobial isolates could tolerate the mimosine considerably. It provides growth advantage to Rhizobium strains that can utilize mimosine. Further, large scale field trials at different geographical locations are required for testing the effectiveness of these rhizobial isolates. Key words: Mimosine degradation, Leucaena leucocephala, Rhizobia <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Syed Farook Ali et al. Screening of Rhizobial Isolates of Leucaena leucocephala Lam. for Mimosine Degradation Ability. Â J Phytol 2/7(2010) 01-06.